Energy scavenging survival kit - Matheyagan A/L Sadarsivam (2023)
This project is about a predominantly design on how solar cell and piezoelectric materials (PZT) can be used as mechanisms to transfer energy from sunlight and vibration into electrical energy that can be stored and used to power other devices. The objectives of this design are to find the appropriate amount of voltage and power distribution for two types of energy scavenger and also the storage device which is the battery and develop an energy harvesting circuit that PZT and solar power can generate. As people carry increasing quantities of mobile appliances around with them, technologies that promise operation without requiring frequent battery replacement or recharging become attractive.